An Exploratory Study of the Dynamics of Marital Adaptation in Chinese-Javanese Couples - Pramudito, Anselmus Agung; Inharjanto, Anselmus; Viona, Reka; Nastiti, Yulia Rasita Hani; Susilawati, Agnes (Universitas Nusa Cendana, 2023)
Inter-ethnic marriages have challenges in the adaptation process due to cultural differences, stereotypes and prejudices between ethnicities. This study aims to explore the dynamics of marital adaptation in Chinese-Javanese couples. The informants in this study are Chinese-Javanese couples who have been married for more than 10 years. The research method used is qualitative with a phenomenological approach. The results of this study found four main aspects in the process of marital adaptation in Chinese-Javanese couples, namely: Cultural adjustment, conflict management, intimacy and egalitarian principles. The further implication of the success of the adaptation process is the sustainability of marital relations in the long term.